Mental health survey of medical personnel during pre-job training in a closed-loop management system during the COVID-19 pandemic - Limin Zhou; Ximei Huang; Liping He; Jiaxin He; Jue Qin; Zhenling Fang; Chen Huang; Jinyu Chen (Frontiers Media S.A., 2023)
ObjectWith the aim of enhancing prevention and regional control of epidemics, the mental health status of medical personnel was analyzed before the implementation of closed-loop management during the COVID-19 pandemic in the regional hospital representative.MethodsIn accordance with directives from the unified deployment of the national and regional health bureaus, and following the inclusion and exclusion criteria, from September 2021 to November 2022, all medical personnel assigned to a closed-loop working environment by Guangzhou Panyu Central Hospital were enrolled as research subjects through cluster sampling method. Using a cross-sectional survey method, relevant data such as age, gender, professional title, and mental health status were collected. The Patient Health Questionnaire-9 (PHQ-9) scale, the Generalized Anxiety Disorder-7 (GAD-7) scale, and the Insomnia Severity Index (ISI) scale were administered. Logistic regression analysis was used to study the influencing factors of depression, anxiety, and insomnia. Single factor logistic regression analysis was performed first, followed by multiple factor logistic regression analysis.ResultsA total of 500 valid responses were received. Depression was reported by a higher proportion of physicians than nurses. Anxiety was reported by higher proportion of men than women and by a higher proportion of physicians than nurses. Medical personnel under the age of 30 years reported fewer symptoms of insomnia than those over the age of 41 years, and medical personnel with intermediate professional titles reported more severe symptoms of insomnia than junior personnel. There was no significant difference between the results of the three questionnaires for medical personnel from other hospital departments or in the different type of closed-loop work environments.ConclusionDuring the pandemic, conducting psychological health assessments for medical personnel undergoing pre-job training in closed-loop management was beneficial for the timely detection of psychological problems. Although this study only conducted a cluster sampling survey and lacked comparative analysis on other medical institutions, it still suggested that it was necessary to strengthen timely psychological counseling and intervention for senior male physicians.